Fetal death: an extreme manifestation of maternal anti-fetal rejection - Lannaman, Kia (J Perinat Med, 2017)
OBJECTIVE: The aim of this study was to determine the association between chronic placental inflammation and amniotic fluid (AF) markers of maternal anti-fetal rejection as well as the presence of microorganisms in the AF fluid of patients with fetal death. STUDY DESIGN: This cohort study included 40 patients with fetal death whose placentas were examined for chronic inflammatory lesions and whose AF chemokine ligand (CXCL)10 and interleukin (IL)-6 concentrations were determined by immunoassays. AF was processed for bacteria, mycoplasmas and viruses using cultivation and molecular microbiologic techniques (i.e. PCR-ESI/MS). RESULTS: (1) The most prevalent placental findings were maternal vascular underperfusion (63.2%, 24/38), followed by chronic inflammatory lesions (57.9%, 22/38); (2) chronic chorioamnionitis (18/38) was three times more frequent than villitis of unknown etiology (6/38); (3) an elevated AF CXCL10 concentration (above the 95th centile) was present in 60% of the cases, and a receiver operating characteristics (ROC)-derived cut-off of 2.9 ng/mL had a sensitivity of 73% and a specificity of 75% in the identification of chronic placental inflammatory lesions; (4) only five cases had microbial invasion of the amniotic cavity, and the presence of microorganisms did not correlate with chronic placental inflammation. CONCLUSION: In women with unexplained fetal death, there is an association between elevated AF CXCL10 and chronic placental inflammatory lesions. Therefore, we conclude that a subset of patients with fetal death may have endured a breakdown of maternal-fetal tolerance, which cannot be attributed to microorganisms in the amniotic cavity.